ILRI 40 years: Livestock and the environment - Steinfeld, H. (International Livestock Research Institute, 2014)
Feature address by Henning Steinfeld (FAO) at the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives, Addis Ababa, Ethiopia, 6–7 November 2014.